The Romanian rural household under the impact of rural development policies - Lorena Chiţea (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
The present paper aims to assess to what extent the rural development policies have had any impact on the Romanian rural household. For this purpose, it was decided to develop a theoretical model for assessing the degree of modernization and socio-economic development of rural areas from the perspective of increasing the rural household welfare. This was achieved taking into consideration the following dimensions of the rural space: natural-anthropic, demographic, social and economic; for each dimension a set of indicators were selected considered relevant for the investigated issue. These indicators lay at the basis of a composite indicator meant to make a diagnosis of the modernization and development degree of the rural area at a given moment, in order to provide proper solutions/directions for rural development policies. To capture the impact of rural development policies on the rural area and on the rural household implicitly, the paper will analyse the correlations between the rural development measures implemented in the programming period 2007-2013 and the composite index of rural modernization and socio-economic development.
Keywords: R20; Q01; O2; 330; rural area; rural household; sustainable development